Hidden treasures, forgotten voices - railway family in chiquinquirá 1960 - 1980: a critical approach from the biographical space and the cultural studies - Reina Vera, Oscar Orlando
This article of reflection presents a critical analysis, based on the following question: What cultural constructions, power relations and identities can be identified in the railway context of Chiquinquirá in the period 1960 – 1980? This is the basis of a research study whose theoretical and conceptual foundations are Cultural Studies, Biographical Space and Memory. In fact, as a result of a careful exploration of narratives provided by some members of the railway family in such a setting, it was built a corpus that was analyzed from a qualitative and hermeneutical perspective. Throughout the process, some cultural aspects of that context were identified. Those aspects reflect specific conceptual categories: culture, power, identity, cultural participation, cultural policy and subjectivities representing the identity traits of that context. This reality shows the role of the North Railway in Chiquinquirá, as well as the cultural roots, planted in this region by this company. As a part of this study, and according to the hermeneutical perspective, the research process currently consists in rewriting a narrated story in order to make this cultural family visible. By the way, this study promotes new proposals in the commitment of giving importance to the wealth of popular memory.